Otimização do processo de secagem para produção de farinha de batata-doce biofortificada - Souza, Diane Maschio de (2019)
The sweet potato cultivation (Ipomoea batatas L. (Lam.)) has a great socioeconomic importance because it is an energetic food, containing a high content of vitamins and minerals. Beauregard cultivar has been gaining prominence in the last years because it presents high productivity and is more nutritious than the conventional varieties cultivated in Brazil, because the orange pulp of this vegetable presents high content of β-carotene. However, this food presents great ease of deterioration during storage, presenting short post-harvest shelf life. Among the methods of food preservation, drying is one of the most widely used post-harvest techniques to preserve the quality of the product, by reducing the water content and thus leading to reduced respiration of the product. This procedure is still essential in obtaining the sweet potato flour. Therefore, the present paper aimed to optimize the process of production of sweet potato flour. Beauregard sweet potato cultivated in experimental field of Fundetec, Cascavel-PR was used as raw material. Sweet potato processing consisted of obtaining the raw material, sanitizing, peeling, cutting, process optimization, convective drying with hot air, grinding and storage. Statistical analysis was performed using a central rotational compound design 23, with three central points and six axial points (totaling 17 assays), evaluating the effects of: concentration of ascorbic acid used in the immersion (g.100mL-1), time of immersion (minutes) and drying temperature (ºC) on the levels of carotenoids, vitamin C, color and protein of the flour. The best processing conditions were defined by the optimization method, choosing the maximum values of carotenoids, vitamin C and protein content, besides smaller values of color luminosity. Concerning carotenoids, a significant effect occurred for all the factors evaluated in the process (p>0,10). The factors acid ascorbic solution (%), immersion time (min) and drying temperature (ºC), contributed to the conservation of carotenoids. For vitamin C, all factors considered in processing were significant, at the significance level. The parameter brightness color was significant at 10% level. The factor ascorbic acid solution did not present a significant diference for the protein response variable, the other factors presented significant response in the process. Simultaneous optimization of the responses enabled obtaining the optimal conditions for the processing of sweet potato flour. The process obtained global desirability of 100%, being the levels of the factor defined in the following conditions: 24.58 μg.100g-1 to vitamin C, 3.64 mg.100g-1 of protein content; 350.45 μg.100g-1 of carotenoids. After optimization, the best results flour was processed again and the sample was characterized for color, carotenoids, vitamin C, moisture, ashes, lipids, crude protein, carbohydrates, caloric content and pH. The experimental design enabled the determination of the best drying conditions of Beauregard sweet potato flour, maintaining high nutritional value.